Alkali‐Metal‐Ion‐Assisted Hydrogen Atom Transfer in the Homocysteine Radical. Issue 7 (12th January 2016) - Lesslie, Michael; Lau, Justin Kai‐Chi; Lawler, John T.; Siu, K. W. Michael; Oomens, Jos; Berden, Giel; Hopkinson, Alan C.; Ryzhov, Victor
Abstract: Intramolecular hydrogen atom transfer (HAT) was examined in homocysteine (Hcy) thiyl radical/alkali metal ion complexes in the gas phase by combination of experimental techniques (ion‐molecule reactions and infrared multiple photon dissociation spectroscopy) and theoretical calculations. The experimental results unequivocally show that metal ion complexation (as opposed to protonation) of the regiospecifically generated Hcy thiyl radical promotes its rapid isomerisation into an α‐carbon radical via HAT. Theoretical calculations were employed to calculate the most probable HAT pathway and found that in alkali metal ion complexes the activation barrier is significantly lower, in full agreement with the experimental data. This is, to our knowledge, the first example of a gas‐phase thiyl radical thermal rearrangement into an α‐carbon species within the same amino acid residue and is consistent with the solution phase behaviour of Hcy radical. Abstract : HAT or no HAT? Conversion of the thiyl radical of homocysteine (Hcy) to the Cα radical via hydrogen atom transfer (HAT; see scheme) is facilitated by complexation with alkali metal ions (M=Li, Na, K). Gas‐phase reactivity and IRMPD spectra of [Hcy−H+ M ] .+ complexes suggest the captodative Cα radical structure, whereas the protonated species [Hcy] .+ remains a thiyl radical.